Evaluation of the Impact of the High-Quality Seedling Assistance Program on Plam Oil Framers’ Income in Bungo District, Jambi - Siti Nurhayati; Muhammad Rachmad R; Rafiqi Rafiqi; Erni Achmad; Muhammad Ridwansyah; Zainul Bahri (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to analyze the comparative income of oil palm farmers who use superior oil palm seeds with farmers who use ordinary oil palm seeds, identify factors that influence oil palm production related to the use of superior seeds, and formulate strategies for the Bungo Regency government in increasing farmers' income through the distribution of superior oil palm seeds. The research method used is a quantitative descriptive method with 99 oil palm farmers as respondents. Data were obtained from primary data through questionnaires and interviews, as well as secondary data sourced from the Central Statistics Agency (BPS) of Jambi Province and Bungo Regency and the Food Crops, Horticulture, and Plantation Service of Bungo Regency. The research results show that the income of farmers using superior oil palm seeds is higher than that of farmers using conventional seeds, due to better plant productivity and higher yield quality. Factors influencing oil palm production include seed quality, plant age, land area, fertilizer use, cultivation techniques, and local government support in the form of extension services and production input assistance. The local government's strategy to increase farmer income is implemented through the distribution of certified superior seeds, technical assistance to farmers, and strengthening farmer institutions. This strategy is expected to increase the productivity and welfare of oil palm farmers in Bungo Regency.